Dr. Károly Ihrig: the Scholar and the Person - Szabó, G. Gábor (Acta Agraria Debreceniensis, 2009)
The paper – in a form of abridged version of an oral presentation – analyses scientific works and  human qualifications of one of the greatest Hungarian scholar, Károly Ihrig. The study deals with the most important works of the great Hungarian polymath on co-operative theory and  agricultural policy, as well as with the story of his works later on.